Diseño de una máquina recolectora para el fruto del árbol de mango variedad Tommy Atkins (mangifera indica L) en la región del Alto Magdalena tolimense (2021)
The present project consists of the design of a machine that allows to carry out the tasks of harvesting the fruit of the Tommy Atkins mango tree, in the Alto Magdalena Tolima region, in a more efficient way. With this, it seeks to reduce the times between harvests and avoid the loss of fruit due to excessive ripening due to delays in harvesting. Another priority factor to keep in mind is the care of the farmer's health by avoiding risks at heights when executing the maneuvers involved in the mango harvest; For this, the design of a machine is carried out that makes it possible to carry out said work